Beyond Gold: Spin‐Coated Ti3C2‐Based MXene Photodetectors. Issue 43 (15th September 2019) - Montazeri, Kiana; Currie, Marc; Verger, Louisiane; Dianat, Pouya; Barsoum, Michel W.; Nabet, Bahram
Abstract: 2D transition metal carbides, known as MXenes, are transparent when the samples are thin enough. They are also excellent electrical conductors with metal‐like carrier concentrations. Herein, these characteristics are exploited to replace gold (Au) in GaAs photodetectors. By simply spin‐coating transparent Ti3 C2 ‐based MXene electrodes from aqueous suspensions onto GaAs patterned with a photoresist and lifted off with acetone, photodetectors that outperform more standard Au electrodes are fabricated. Both the Au‐ and MXene‐based devices show rectifying contacts with comparable Schottky barrier heights and internal electric fields. The latter, however, exhibit significantly higher responsivities and quantum efficiencies, with similar dark currents, hence showing better dynamic range and detectivity, and similar sub‐nanosecond response speeds compared to the Au‐based devices. The simple fabrication process is readily integratable into microelectronic, photonic‐integrated circuits and silicon photonics processes, with a wide range of applications from optical sensing to light detection and ranging and telecommunications. Abstract : Ti3 C2 ‐based MXene contacts —spin‐coated from an aqueous colloidal suspension onto a GaAs substrate—are compared with vacuum‐deposited titanium/gold electrodes for the photodetection of light. Such an MXene‐based device has better detectivity, quantum efficiency, and a higher dynamic range as compared to the conventional Au‐based metal–semiconductor–metal devices.